Parodia hofackeriana (Cactaceae—Notocacteae), a new species from southwest of Rio Grande do Sul, Brazil - Silveira De Oliveira, Anabela; Corrêa Pontes, Rodrigo (Phytotaxa, 2023)
The South American genus Parodia includes taxa that are not sufficiently known from the taxonomical point of view. Based on field surveys, and review of nomenclatural types, specimens, and literature, we found an interesting species of Parodia from rocky areas in the southwest region of Rio Grande do Sul, which is here described as Parodia hofackeriana sp. nov. Geographic distribution, phenology, habitat, conservation, and morphological affinities with related species are provided.